The Rise of African American Women Judges During the Past Century - Judge Sandra Farragut-Hemphill; Ebony McCain (Washington University Journal of Law and Policy, 2022)
Ascension to the bench for African American women has historically been slow. At the formation of the Mound City Bar Association in 1922, there were few African American women lawyers in the United States. Nearly a century later in 2020, a rapidly increasing number of African American women have joined state and federal courts in Missouri and across the country. This Article documents the rise of African American women judges that has occurred over recent decades. The authors assert that the elevation of African American women jurists positively affects both perceptions of our legal system and the outcomes of judicial decision- making in this country. Despite the advancement of these accomplished jurists, the authors suggest that significant work still remains in obtaining an equitable racial and gender representation in the judiciary.
Keywords: African American Women Judges; Judiciary